ICT based Wireless Sensor Network for Retracing the Parked Vehicle - John, Neethu Maria; Kurian, Simy Mary; Vijayan, Vinodh P (International Journal of Computer Sciences and Engineering, 2025)
It is normal to be in the following 100 years, world's most extreme populace will be living in urban areas. Henceforth the utilization of vehicle and its connected administrations will be vital. As the quantity of vehicles increases, parking of the vehicle in urban communities will be testing issue, particularly concerning contamination and keeping up with the eco arrangement of the area. Many individuals are not intrigued to utilize conventional or robotized stopping region as a result of the trouble they face during the utilization. Indeed, even individuals find it hard to follow the return way to their own vehicle. The bigger number of shrewd vehicle leaving frameworks is executed in different nations which typically take care of the issue of parking spot and powerful use of utilities. Yet, in a profoundly populated region security of individuals in a leaving opening and following of the vehicle will be extremely difficult because of its tendency of heterogeneous individuals and assortment of vehicles. An IOT empowered Sensor network based Advanced parking spot with camera and sound sensors will actually want to gather enormous measure of information which can be used to create intriguing example utilizing appropriate AI algorithms